Correct determination of alcoholic strength in alcoholic products - Kolesnov Alexander; Charapitsa Siarhei; Sytova Svetlana; Kavalenka Anton; Sabalenka Lidziya; Zayats Mikhail; Leschev Sergey (BIO Web of Conferences, 2023)
The paper describes a method, which combines sample density measurement data and gas chromatographic data to determine the quantitative content of volatile compounds, including ethyl alcohol, in sample. This approach can improve the accuracy of alcohol content measurements. The proposed method takes into account the presence in sample of congeners, such as methanol, fusel oils, esters and etc. The experimental study of 8 brandy samples was carried out. All samples were distillated and measured by GC-FID. The volatile compounds identified in the analyzed distillates were acetaldehyde, isobutanal, ethyl acetate, methanol, butan-2-ol, propan-1-ol, 2-methylpropan-1-ol, isoamyl acetate, butan-1-ol, 3-methylbutan-1-ol, ethyl caproate, ethyl lactate, hexanol, cis-3-hexen-1-ol, ethyl caprylate, furfural, ethyl caprate, ethyl laurate and 2-phenylethanol. The quantitative determination of congeners was carried out using ethanol as a reference substance. The sum of volume content of detected congeners in studied distillates ranged from 0.28 to 0.46%. The absolute difference between results for determination of alcoholic strength using only water-ethanol tables (traditional method) and combination of data from water-ethanol tables and gas chromatography data (proposed method) ranged from 0.22 to 0.40%.